2016
DOI: 10.1177/0021998316632602
|View full text |Cite
|
Sign up to set email alerts
|

Study on the reinforcing mechanisms of nano silica to cement-based materials with theoretical calculation and experimental evidence

Abstract: Cement mortars with different contents of nano silica (NS) were fabricated and tested. Their compressive and flexural strengths showed significant increases. Theoretical calculation and thermogravimetry (TG) analysis, scanning electron microscope (SEM) and X-Ray powder diffraction (XRD), and electrical resistivity test were used to analyze the reinforcing mechanisms of NS. Theoretically, consumed calcium hydroxide (CH) increases with NS content, which indicates that NS has huge potential to react with CH. Acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(18 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…The process of fabricating nano-engineered cementitious composites is as follows: 1) Water, superplasticizer and nano fillers were mixed by glass bar and then sonicated to form a suspension; 2) Cement and aggregate were put into the suspension slowly in stir pan and mixed by agitator; 3) The mixture was poured into the oiled mould and the mould was put on the electric vibrator in order to eliminate bubbles; 4) All nano-engineered cementitious composites were cured at temperature of 20°C in 95% relative humidity for 24 h before demold. Then specimens were cured in water at 20±1°C until the curing age [6,19]. Three test specimens were fabricated for each cementitious material.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of fabricating nano-engineered cementitious composites is as follows: 1) Water, superplasticizer and nano fillers were mixed by glass bar and then sonicated to form a suspension; 2) Cement and aggregate were put into the suspension slowly in stir pan and mixed by agitator; 3) The mixture was poured into the oiled mould and the mould was put on the electric vibrator in order to eliminate bubbles; 4) All nano-engineered cementitious composites were cured at temperature of 20°C in 95% relative humidity for 24 h before demold. Then specimens were cured in water at 20±1°C until the curing age [6,19]. Three test specimens were fabricated for each cementitious material.…”
Section: Methodsmentioning
confidence: 99%
“…achieved. An addition of 1.5% nano-sillica (NS) increased the 3d compressive and flexural strengths by 45.6% and 18.4%, respectively [6]. Meanwhile, the addition of NS can increase the freeze-thaw resistance, chloride penetration and permeability, abrasion resistance and fire resistance of cementitious composites [7][8][9][10].…”
mentioning
confidence: 99%
“…A sample of nanosilica can be seen in Figure 4 . The experiments carried out by Zhang et al [ 138 ] show the potential of the reinforcement of nanosilica: with 2% w/c of this particles, a 48.7% and 16.0% improvement in compressive and flexural strengths was achieved, respectively, in ordinary mortar. Zhang et al dispersed the particles with the ultra-sonication method.…”
Section: Nanoinclusionsmentioning
confidence: 99%
“…Gonzalez et al found that the durability and strength of concretes were improved with nanoparticle inclusion [18]. The investigation of Zhang et al indicated that 2% of content nanoparticles to cementitious composites greatly enhanced flexural and compressive strengths [19]. A 38% increase in tensile strength of the cement pastes containing 2% nanoparticles was obtained by Gesoglu et al [20].…”
Section: Introductionmentioning
confidence: 99%